Airline’s business performance indicators and their impact on operational efficiency - Alexandre Pinchemel; Mauro Caetano; Ricardo Messias Rossi; Marco Antônio Silva (BBR: Brazilian Business Review)
Airlines must constantly evaluate the costs and efficiency of their operational performance indicators to establish a competitive business market strategy. This study aims to investigate the relevance of some performance indicators of airline´s management and operational efficiency. With the use of a panel data regression for the four largest private Brazilian airlines - Avianca, Azul, Gol, and Latam, from 2009 to 2017, the results show that operational efficiency is achieved when there is a greater offer of routes and flight frequency to meet passenger demand, generating higher revenue passenger kilometer (RPK). On the other hand, shorter stage length and reduced takeoff numbers affect inversely proportional the operating efficiency as a function of fuel consumption and energy capacity. Through the analysis of these performance indicators, it is possible to determine strategies that support decision making to increase the operational efficiency of airlines.